Pengukuran Dasar Telaga menggunakan Alat Perum Gema Untuk Menghasilkan Peta Batimetri di Telaga Winong Yogyakarta - Erik Febriarta; Septian Vienastra; Agus Suyanto; Ajeng Larasati (Universitas Negeri Yogyakarta, 2020)
Lake Winong is one lake that is not dried on dry season. This lake is located in the Village Kepek, District Saptosari, Gunung Kidul Regency, Special Region Province Yogyakarta. This study was designed to determine the depth or bottom topography of Lake Winong to produce bathymetry maps. Firstly, a survey was conducted to measure the depth with an echosounder instrument. Principally, an echosounder records the time interval required by the emitted sound wave to propagate to the bottom and return, from which the distance or depth (m) can be computed. Secondly, the depth data were interpolated by initially cross-validating the smallest Root Mean Squared Errors (RMSE) of the Inverse Distance Weighting (IDW), kriging, and natural neighbor methods. Each was run with the power values (weight factors) of 0.5, 1, 2, and 3. The results showed that kriging interpolation with a power value of 3 yielded the smallest RMSE, namely 0.005, and the lake observed was -0.2 to -1.8 m deep, with the deepest location found in the middle of the lake.